Magnetic nanocomposites based on borate glasses doped with Fe and Mn - Edelman, I.S.; Ivantsov, R.D.; Ivanova, O.S.; Bayukov, O.A.; Zaikovskii, V.V. (Functional Materials, 2006)
Magnetic properties, including magneto-optical Faraday Effect (FE), have been investigated in potassium-aluminum-boron glasses doped with iron and manganese oxides. The formation of magnetic nanoparticles has been proved using high resolution electron microscopy. A wide variety of particle size, shape, structure, and distribution in the matrix has been observed depending on the technological conditions. The narrow region of conditions has been established providing formation of almost ideal manganese ferrite single crystals of about 40 nm size distributed rather homogeneously in the matrix. Therefore, the glasses can be considered as a nano-composite material. Thanks to the low concentration of paramagnetic elements, the glasses kept the optical transparence and demonstrated high FE in the infrared and a part of the visible spectral regions, thus making it possible to develop a new magneto-optical material for the 1.0-1.5 μm spectral region. Исследованы магнитные свойства, включая магнитооптический эффект Фарадея (FE), в калиево-алюмо-боратных стеклах, допированных оксидами марганца и железа. С помощью электронной микроскопии высокого разрешения доказано формирование магнитных наночастиц. Наблюдалось большое разнообразие размеров, формы, структуры частиц и их распределения в матрице в зависимости от технологических условий. Установлена узкая область условий, обеспечивающих формирование почти идеальных монокристаллов марганцевого феррита размером 40 нм, довольно равномерно распределенных в матрице. Поэтому исследованные стекла можно рассматривать как нано-ком-позитный материал. Благодаря низкому содержанию парамагнитных элементов, стекла сохраняют оптическую прозрачность и демонстрируют высокие значения FE в инфракрасной и части видимой области спектра, что позволяет предпринять усилия по созданию нового магнитооптического материала для области спектра 1,0-1,5 мкм. Магнітні властивості, включаючи магнето-оптичний ефект Фарадея (ЕФ), досліджено на калій-алюміній-боратному склі, легованому окислами заліза та марганцю. Формування магнітних нано-часток доведено за допомогою електронного мікроскопа високої роздільної здатності. Спостерігався широкий діапазон розмірів часток, форми, структури та розподілення у матриці, в залежності від технологічних умов. Встановлено вузьку область умов, в якій формувалася майже ідеальна монокристалічна структура марганцевого фериту, розміром 40 нм, достатньо випадково розподілена у матриці. Отже, скло можна вважати нанокомпозитним матеріалом. Завдяки низькій концентрації парамагнітних елементів, скло зберігало оптичну прозорість та мало високий ЕФ в інфрачервоній та видимій спектральних областях, що дозволило створити нові магнето-оптичні матеріали для спектрального діапазону 1.0 1.5 μм.